CLINICAL USES AND APPLICATION OF WITHANIA SOMNIFERA (ASHWAGANDHA): IN DENTISTRY: A NARRATIVE REVIEW - Dr. Lakshmi Thribhuvanan, Dr. M. S. Saravanakumar, Dr Yashika Hans, Dr Clins Thankachan, Dr Mitushi Singh, Dr.Lakshmi Thribhuvanan (Chelonian Research Foundation, 2023)
Dental health have always been an area of upwardly displaced threshold gaining a widespread global importance in the health and wellness scenario. The higher incidence of all dental conditions with dental caries being the habitual one still calls upon to be an high priority health concern globally with its indefinitive grasp entangling populations in an unbiased manner and classification. The treatment and management of dental health issues continue to persist at its peak due to uphilling demand and rise of expensive dental services and dental products which aberrantly remains from the outreach of customary members of the local communities prevailing in developing nations. The predominant absence of any available dental insurance schemes and highly inaccessibly monetary demands still pursuits the dependent categories from indulging into accepting any forms of dental services inclined for their beneficiary needs thereby enthrusting the precedence for the maintenance of their general health over their dental demands. Researchers and health promoters including clinicians have been in a constant effort to amend treatment modalities with the existent dental products and thereby deliver these dental services in a cost effective manner as possible. A vast majority of the commercially available products which are notably advantageous and utilized in rendering the most acceptable dental treatment still persist with high monetary demands along with existent cytotoxic and reliable side effects. Withania somnifera (Ashwagandha) is one of the most important Indian herb displaying high medicinal values which is distributed widely in Indian subtropical regions. Withania somnifers have been deeply evaluated and studied for its higjly acclaimable medicinal benefits, hence this review will evaluate the profound applications of Withania somnifera in dentistry. Key Words: Withania somnifera, Herbal, Dentistry